DIGITAL-BASED AKHLAK LEARNING THROUGH CANVA POSTER MAKING: A CASE STUDY AT AN ISLAMIC ELEMENTARY SCHOOL - Kholifah, Siti Nur; Fa’atin, Salmah; Sholihuddin, Moh (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
Purpose: This study aims to analyze the process and influence of character education based on the Canva application at SD IT Mamba'ul Ulum Jepara. Method: The approach used is a qualitative case study, with data collected through observation, interviews, and documentation of PAI teachers and sixth-grade students. Result: The results show that the use of Canva creates interactive, collaborative, and creative learning. Students not only understand the values of honesty, empathy, and environmental awareness cognitively, but also internalize them through the creation of digital posters. Conclusion: The digital graphic design platform (Canva) serves as an instrument for internalizing moral values, transforming conventional methods into a visual-creative approach that is relevant to the alpha generation. Implication: This research contributes an innovative model for Islamic character education in the digital age, proving that technology not only serves as a technical tool but also as an effective medium for transforming spiritual and moral values holistically. This study recommends the use of digital creative media to enhance students' motivation and digital literacy skills in religious education.